STABILITY OF FISCAL REVENUES IN EU: WHAT TO TAX? - Karpowicz Andrzej; Tazhbenova G.; Tulegenova Zh.; Orynbekova G. (Scientific Journal of Pedagogy and Economics, 2020)
Certain and predictable tax revenues are desirable by states to run fiscal policy smoothly and minimize any negative effects of business cycles. Over the last decades sizes of government budgets in most EU Member States have experienced rather small transformations. However, particular kinds of taxes contribute to that stability to different extent. Although, this matter is important from the perspective of state budget, it has not been analysed thoroughly before – especially in EU. Based on statistical analysis of macroeconomic data I calculated that revenues from payroll taxes feature especially low variability and positively influence the budget constancy. Changes over time are slightly bigger for taxes imposed on production. Inflows from taxation of income of corporations are particularly unstable. These findings may support policymakers in appropriate budget revenues design. Expansionary fiscal policy is believed to boost economic growth ( (Aschauer, 1989), (Munnell, 1990)). Public investments are traditionally believed to support long-term growth of economies (Barro, Government Spending in a Simple Model of Endogenous, 1990). On the other hand low taxes should support development of economy as well ((Engen & Skinner, 1992), (Daveri & Tabellini, 2000), (Karras & Furceri, 2009), (Padovano & Galli, 2001) or (Lee & Gordon, 2005) to mention only selected research). For example Romer and Romer estimated that a 1% increase in taxation relative to GDP induces reduced output of up to 3% over the following three years (Romer & Romer, 2007). Mountford and Uhling claimed that tax cuts - even if financed from budget deficit – are most effective from the perspective of economy growth (Mountford & Uhlig, 2008). Blanchard and Perotti found that tax shocks affect investment, consumption and output (Blanchard & Perotti, 2002). However, some empirical analysis failed to confirm significance of the relation between GDP and tax rates ((Easterly & Rebelo, 1993), (Mendoza, Milesi-Ferretti, & Asea, 1997)). The correlation between the level of the tax rate and output was found to be indeed negative but sometimes non-existing. These results are in line with common sense. However, in the long run high public spending cannot be combined with low taxes (assuming that low taxes transfer into smaller budget revenues). High public deficits, which may arise in consequence of expansionary fiscal policy, are eventually harmful for economic growth in the long-run. Therefore, satisfactory inflows from taxes are desirable. Maintaining balanced budgets is a typical objective of several world economies. Yet this requirement seems key for European Monetary Union states, which use single currency and hence lead common monetary policy [1]. To improve economic stability of those countries and to provide for at least impeded policy-mix tools, certain requirements related to fiscal policy were imposed on them. According to the so called Convergence Criteria (also known as Maastricht Criteria)(i) the ratio of the annual government deficit to GDP must not exceed 3 percent and (ii) the ratio of government debt to GDP must not exceed 60 percent. However, several Member States are struggling against high budget deficits which are followed by excessive public debts. Most EU Member States have been returning to balance over last years and in 2017 almost half of them recorded government surplus. However, the budget deficit for the EU as a whole is still substantial and in 2017 amounted to 81.6% of its GDP. This is far more than before the crisis in 2007 when a figure of 57.5% of GDP was recorded. Moreover, although from peak in 2014 general government debt decreased on average in a number of Member States, still in 2017 as much as 12 out of 19 eurozone countries bound by the Maastricht criteria recorded debt above required level of 60% of local GDP. Identification of reliable sources of state revenues may provide a useful tool to cope with that issues.